Social Change According to Badiuzzaman Nursi and Ali Shariati: Comparative Inquiry - Ramdane, Tahraoui; Souad, Merah (2017)
Throughout the course of Islamic revivalism history, many prominent Muslim reformists left a great impact on the actual Islamic world view. They left their marks in the efforts of lifting the Muslim Ummah up from the state of decline and backwardness. • Theses efforts varied tremendously due to the social, intellectual, sectarian and political background of these reformists. However, it is safe to say that all of their efforts were brave attempts to cross the borders of division among Muslims and propose an Islamic framework for change. • In this presentation we will explore the differences between Badiuzzaman Nursi's `gradualist', `progressive' approach and Ali Shariati `revolutionary‘ approach to generate social change.